Abortive base-excision repair of radiation-induced clustered DNA lesions in Escherichia coli - Blaisdell, Jeffrey O. (The National Academy of Sciences, 2001)
It has been postulated that ionizing radiation produces a unique form of cellular DNA damage called “clustered damages” or “multiply damaged sites”. Here, we show that clustered DNA damages are indeed formed in Escherichia coli by ionizing radiation and are converted to lethal double-strand breaks during attempted base-excision repair. In wild-type cells possessing the oxidative DNA glycosylases that cleave DNA at repairable single damages, double-strand breaks are formed at radiation-induced clusters during postirradiation incubation and also in a dose-dependent fashion. E. coli mutants lacking these enzymes do not form double-strand breaks postirradiation and are substantially more radioresistant than wild-type cells. Furthermore, overproduction of one of the oxidative DNA glycosylases in mutant cells confers a radiosensitive phenotype and an increase in the number of double-strand breaks. Thus, the effect of the oxidative DNA glycosylases in potentiating DNA damage must be considered when estimating radiation risk.